2012
DOI: 10.1126/science.1215647
|View full text |Cite
|
Sign up to set email alerts
|

Analytic Thinking Promotes Religious Disbelief

Abstract: Scientific interest in the cognitive underpinnings of religious belief has grown in recent years. However, to date, little experimental research has focused on the cognitive processes that may promote religious disbelief. The present studies apply a dual-process model of cognitive processing to this problem, testing the hypothesis that analytic processing promotes religious disbelief. Individual differences in the tendency to analytically override initially flawed intuitions in reasoning were associated with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
416
6
12

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 472 publications
(474 citation statements)
references
References 32 publications
40
416
6
12
Order By: Relevance
“…It therefore stands to reason that education negatively predicts a tendency to embrace relatively simplistic explanations for complex events. Consistently, research found that education level is associated with disbelief in paranormal phenomena, a finding that was mediated by analytic thinking—that is, deliberative and conscious information processing (Aarnio & Lindeman, 2005; see also Gervais & Norenzayan, 2012). These arguments are relevant for belief in conspiracy theories, which is correlated with belief in paranormal phenomena (e.g., Darwin, Neave, & Holmes, 2011), and which also has been described as a simplification of reality.…”
Section: Mediators Of the Education–conspiracy Linkmentioning
confidence: 91%
See 1 more Smart Citation
“…It therefore stands to reason that education negatively predicts a tendency to embrace relatively simplistic explanations for complex events. Consistently, research found that education level is associated with disbelief in paranormal phenomena, a finding that was mediated by analytic thinking—that is, deliberative and conscious information processing (Aarnio & Lindeman, 2005; see also Gervais & Norenzayan, 2012). These arguments are relevant for belief in conspiracy theories, which is correlated with belief in paranormal phenomena (e.g., Darwin, Neave, & Holmes, 2011), and which also has been described as a simplification of reality.…”
Section: Mediators Of the Education–conspiracy Linkmentioning
confidence: 91%
“…To measure analytic thinking I used the Cognitive Reflection Test (Frederick, 2005; see also Gervais and Norenzayan, 2012). This measure is designed to assess participants' analytic thinking skills through three mathematical questions, where the correct answer deviates from the intuitive answer that one is likely to arrive at if one does not use analytic thinking (e.g., ‘A bat and a ball cost 1.10 Euros.…”
Section: Methodsmentioning
confidence: 99%
“…. .naturally biased to view nature as though it is intentionally created', [8], p. 77), has resonated throughout the cognitive sciences, influencing interpretations of concept development [9][10][11][12][13] science learning [8,14], religion and morality [15][16][17][18][19][20], and cross-cultural reasoning [7].…”
Section: Are Clouds 'For' Raining?mentioning
confidence: 99%
“…plusieurs groupes intermédiaires avec des valeurs, des normes et des pratiques différentes, a érodé la structure de la plausibilité de la société et il a comme effet un degré d'intégration plus bas, un moindre degré d'observation de normes religieuses (personnalisées), moins de participation et de membres de l'église (Hak et Sanders, 1996). Les procès cognitifs peuvent aussi stimuler l'incrédulité, puisque « as some individuals are more prone to analytically override initially flawed intuitions in reasoning » (certains individus sont plus susceptibles à outrepasser analytiquement des intuitions de raisonnement au début affaiblis que des autres) (Gervais et Norenzayan, 2012). Martin (2005 : 7) souligne la relevance des contextes dans le procès : « the theory of secularization … is profoundly inflected by particular histories » (la théorie de la sécularisation est profondément infléchie par des histoires particulières) tandis qu'il ne voit pas « [a] consistent relation between the degree of scientific advance and a reduced profile of religious influence, belief and practice » (de relation cohérente entre le degré d'avancement scientifique et un profil réduit d'influence religieuse, de croyance et de pratique religieuse) (Martin, 2005 : 119).…”
Section: La Sécularisation Et Le Déclin Des Pratiques Religieusesunclassified